Anaerobic Toluene Catabolism of Thauera aromatica: the bbs Operon Codes for Enzymes of β Oxidation of the Intermediate Benzylsuccinate - Leuthner, Birgitta (American Society for Microbiology, 2000)
The pathway of anaerobic toluene oxidation to benzoyl coenzyme A (benzoyl-CoA) consists of an initial reaction catalyzed by benzylsuccinate synthase, a glycyl radical enzyme adding the methyl group of toluene to the double bond of a fumarate cosubstrate, and a subsequent β-oxidation pathway of benzylsuccinate. Benzylsuccinate synthase has been studied in some detail, whereas the enzymes participating in β oxidation of benzylsuccinate are unknown. We have investigated these enzymes by analyzing substrate-induced proteins in toluene-grown cells. Toluene-induced proteins were identified and N-terminally sequenced. Nine of these proteins are encoded by an 8.5-kb operon consisting of bbs (beta-oxidation of benzylsuccinate) genes whose products are apparently involved in the β-oxidation pathway of benzylsuccinate. Two of the genes, bbsE and bbsF, code for the subunits of a succinyl-CoA:benzylsuccinate CoA-transferase whose activity was previously detected in toluene-grown Thauera aromatica. The bbsG gene codes for a specific benzylsuccinyl-CoA dehydrogenase, as confirmed by overexpression of the gene in Escherichia coli and detection of enzyme activity. The further enzymes of the pathway are probably encoded by bbsH (enoyl-CoA hydratase), bbsCD (3-hydroxyacyl-CoA dehydrogenase), and bbsB (3-oxoacyl-CoA thiolase). The operon contains two additional genes, bbsA and bbsI, for which no obvious function could be derived. The bbs operon is expressed only in toluene-grown cells and is regulated at the transcriptional level. Promoter mapping revealed a transcription start site upstream of the bbsA gene. This represents the first known promoter site in Thauera spp.